Susceptibility breakpoint for cefquinome against Escherichia coli and Staphylococcus aureus from pigs - Hui-lin ZHANG; Yi-yang ZHAO; Zi-chong ZHOU; Huan-zhong DING (Journal of Integrative Agriculture, 2021)
Cefquinome is the only fourth-generation cephalosporin used solely for veterinary applications. In this study, we established the wild-type cut-off (COWT) and pharmacokinetic/pharmacodynamic cut-off (COPD) of cefquinome against Escherichia coli and Staphylococcus aureus. A total of 210 E. coli and 160 S. aureus isolates were collected from pigs in Guangdong Province between 2014 and 2018. The minimum inhibitory concentrations (MICs) were determined using a microdilution broth method. MIC50 and MIC90 were 0.06 and 0.25 μg mL−1 for E. coli and 0.5 and 1 μg mL−1 for S. aureus, respectively. Statistical analysis and the ECOFFinder Program showed that the COWT for cefquinome against E. coli and S. aureus were 0.125 and 2 μg mL−1, respectively. The resistance rates were 11.9% for E. coli and 6.25% for S. aureus. Based on a 5000-subject Monte Carlo simulation, the COPD value for cefquinome against E. coil and S. aureus was 0.25 μg mL−1 under the recommended dose (2 mg kg−1, twice a day for 3 days), confirming that infections caused by strains with MIC≤0.25 μg mL−1 could be effectively treated. Following adjustment of the dosing regimen to 4.5 mg kg−1, effective treatment (>90) was achieved for S. aureus infections with MIC90 1 μg mL−1. This susceptibility breakpoint determination is significant for resistant surveillance and cefquinome dosage guidance against E. coli and S. aureus in pigs.